The paediatric version of Wisconsin gait scale, adaptation for children with hemiplegic cerebral palsy: a prospective observational study - Agnieszka Guzik; Mariusz Drużbicki; Andrzej Kwolek; Grzegorz Przysada; Katarzyna Bazarnik-Mucha; Magdalena Szczepanik; Andżelina Wolan-Nieroda; Marek Sobolewski (BMC, 2018)
Abstract Background In clinical practice there is a need for a specific scale enabling detailed and multifactorial assessment of gait in children with spastic hemiplegic cerebral palsy. The practical value of the present study is linked with the attempts to find a new, affordable, easy-to-use tool for gait assessment in children with spastic hemiplegic cerebral palsy. The objective of the study is to evaluate the Wisconsin Gait Scale (WGS) in terms of its inter- and intra-rater reliability in observational assessment of walking in children with hemiplegic cerebral palsy. Methods The study was conducted in a group of 34 patients with hemiplegic cerebral palsy. At the first stage, the original version of the ordinal WGS was used. The WGS, consisting of four subscales, evaluates fourteen gait parameters which can be observed during consecutive gait phases. At the second stage, a modification was introduced in the kinematics description of the knee and weight shift, in relation to the original scale. The same video recordings were rescored using the new, paediatric version of the WGS. Three independent examiners performed the assessment twice. Inter and intra-observer reliability of the modified WGS were determined. Results The findings show very high inter- and intra-observer reliability of the modified WGS. This was reflected by a lack of systematically oriented differences between the repeated measurements, very high value of Spearman's rank correlation coefficient 0.9 ≤ |R| < 1, very high value of ICC > 0.9, and low value of CV < 2.5% for the specific physical therapists. Conclusions The new, ordinal, paediatric version of WGS, proposed by the authors, seems to be useful as an additional tool that can be used in qualitative observational gait assessment of children with spastic hemiplegic cerebral palsy. Practical dimension of the study lies in the fact that it proposes a simple, easy-to-use tool for a global gait assessment in children with spastic hemiplegic cerebral palsy. However, further research is needed to validate the modified WGS by comparing it to other observational scales and objective 3-dimensional spatiotemporal and kinematic gait parameters. Trial registration anzctr.org.au, ID: ACTRN12617000436370. Registered 24 March 2017.